Pengaruh Pelatihan Pemusatan Perhatian (Mindfulness) Terhadap Peningkatan Empati Perawat - Umniyah Umniyah; Tina Afiatin (Universitas Islam Indonesia, 2009)
This research is aimed to recognize the effect of minduliness training to enhance the empathy level of healthcare professionals (nurse). The design of this research is randomized pretest-posttest control group design. The instrument of measurement in this research is Empathy Scale, observation, interview and sharing ideas. The result of the one way anova analysis indicated that there was a significant difference of empathy score in post-test measurement between experimental group and control group, which F = 20,724;p - 0,001 (p <0,05). It means that minduliness training was effective for enhancing the empathy level of healthcare professional (nurse).Key words: empathy, mindfulness, healthcare professionals (nurse).